The Effect of Environmental Performance and Corporate Social Responsibility Disclosure on Financial Performance of Energy Sector Companies Listed on the Indonesia Stock Exchange for the 2021-2024 Period - Syifa Maulida Dewi; Neni Maryani; Adelia Nidyanti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of environmental performance and corporate social responsibility disclosure on financial performance in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This study employed a quantitative approach using secondary data obtained from annual reports, sustainability reports, and PROPER ratings. The population consisted of energy sector companies listed on the Indonesia Stock Exchange, while the sample was selected using a purposive sampling method, resulting in 22 companie with 88 samples.. Data were analyzed using multiple linear regression. The results showed that environmental performance had no effect on financial performance, while corporate social responsibility disclosure had a positive effect on financial performance. The results simultaneously show that environmental performance and corporate social responsibility disclosure have an impact on financial performance.